Smooth muscle cell sheet transplantation preserve cardiac function and minimize cardiac remodeling in a rat myocardial infarction model. Issue 1 (December 2016) - Harada, Shingo; Nakamura, Yoshinobu; Shiraya, Suguru; Fujiwara, Yoshikazu; Kishimoto, Yuichiro; Onohara, Takeshi; Otsuki, Yuki; Kishimoto, Satoru; Yamamoto, Yasutaka; Hisatome, Ichiro; Nishimura, Motonobu
Abstract Background We examined whether a vascular smooth muscle cell (SMC) sheet is effective in the treatment of a rat myocardial infarction (MI) model. Methods We examined the effect of SMC sheet on the cardiac function and cardiac remodeling in a rat MI model in comparison with their effect of dermal fibroblast (DFB) sheet in vivo. Furthermore, we estimated the apoptosis and secretion of angiogenic factor of SMC under hypoxic condition in comparison with DFB. Seven days after MI, monolayer cell sheets were transplanted on the infarcted area (SMC transplantation group, SMC-Tx; DFB transplantation group, DFB-Tx; no cell sheet transplantation group, Untreated; neither MI nor cell sheet transplantation group, Sham). We evaluated cardiac function by echocardiogram, degree of cardiac remodeling by histological examination, and secretion of angiogenic growth factor by enzyme immunoassay. Results Twenty-eight days after transplantation, SMC-Tx showed the following characteristics compared with the other groups: 1) significantly greater fractional area shortening (SMC-Tx, 32.3 ± 2.1 %; DFB-Tx, 23.3 ± 2.1 %; untreated, 25.1 ± 2.6 %), 2) suppressed left ventricular dilation, smaller scar expansion, and preserved wall thickness of the area at risk and the posterior wall, 3) decreased fibrosis, preserved myocardium in the scar area, and greater number of arterioles in border-zone, 4) tight attachment of SMC sheets on the scarred myocardium, and less apoptotic cell death. In in vitro experiments, SMCs secreted higher amounts of basic fibroblast growth factor (SMC, 157.7 ± 6.4 pg/ml; DFB, 3.1 ± 1.0 pg/ml), and showed less apoptotic cell death under hypoxia. Conclusions Our results illustrate that transplantation of SMC sheets inhibited the progression of cardiac remodeling and improve cardiac function. These beneficial effects may be due to superior SMC survival.